2023
DOI: 10.1002/pul2.12227
|View full text |Cite
|
Sign up to set email alerts
|

RASA3 is a candidate gene in sickle cell disease‐associated pulmonary hypertension and pulmonary arterial hypertension

Abstract: Pulmonary hypertension (PH) is associated with significant morbidity and mortality. RASA3 is a GTPase activating protein integral to angiogenesis and endothelial barrier function. In this study, we explore the association of RASA3 genetic variation with PH risk in patients with sickle cell disease (SCD)‐associated PH and pulmonary arterial hypertension (PAH). Cis ‐expression quantitative trait loci (eQTL) were queried for RASA3 using whole genome genotype arrays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The SNP rs9525228 correlated with PH risk, higher TRV values and higher pulmonary vascular resistance. Moreover, it was associated with precapillary PH values and decreased survival in a subgroup of the patients [64]. The above results are summarized in Table 1.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 78%
See 1 more Smart Citation
“…The SNP rs9525228 correlated with PH risk, higher TRV values and higher pulmonary vascular resistance. Moreover, it was associated with precapillary PH values and decreased survival in a subgroup of the patients [64]. The above results are summarized in Table 1.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 78%
“…Another reasonable approach for future studies is to examine SCD patients for polymorphisms identified in patients with idiopathic pulmonary arterial hypertension, unrelated to SCD.For example, Tang et al, (2022), suggested several genes as possible markers for PH pathogenesis and potential targets for the prevention of pulmonary vascular restructure including SLC4A1, AHSP, ALAS2, CA1, HBD, SNCA, HBM, SELENBP1, SERPINE1, ITGA2B, TEAD4, TGIF2LY, GATA5, GATA1, GATA2, and FOS [67].It would be interesting to investigate whether these data can be confirmed in SCD, with special attention to the ancestral composition of the patient population. The recent identification of the RASA3 gene as a candidate gene involved in the pathogenesis and prognosis of PH in SCD as well as pulmonary arterial hypertension in non-SCD patients is also an important finding [64]. Validation of each study in larger groups as well as wider ancestral groups is necessary to confirm causative associations.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs9525228 correlated with PH risk, higher TRV values, and higher pulmonary vascular resistance. Moreover, it was associated with precapillary PH values and decreased survival in a subgroup of patients [75]. The above results are summarized in Table 2.…”
Section: Role Of Gene Polymorphisms In Pathogenesis and Prognosis Of ...mentioning
confidence: 79%
“…It would be interesting to investigate whether these data can be confirmed in SCD, with special attention on the ancestral composition of the patient population. The recent identification of the RASA3 gene as a candidate gene involved in the pathogenesis and prognosis of PH in SCD, as well as pulmonary arterial hypertension in non-SCD patients, is also an important finding [75]. Validation of each study with larger groups as well as broader ancestral groups is necessary to confirm causative associations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the microvascular factors, the common background of SCD, di cultly can be evaluated quantitatively. In every way, the primary role played by PAH in promoting RV damage and a consequent chain of adverse cardiac events is evident, so much to hypothesize the interfering action of other genes, still unknown [4].…”
Section: Discussionmentioning
confidence: 99%